Penerapan Zpreneur Dengan Tehnik Gamifikasi Berupa Transfer Armo Untuk Meningkatkan Kualitas Pembelajaran - Qurotul Aini; Danny Pratama; Novita Heriyani (UNIVERSITAS RAHARJA, 2017)
Along with the development of technology that the sooner make the College began to improve competitiveness in terms of technology and information education. Rapid improvement from year to year make Raharja College want to always innovate, be creative and make an innovation that will benefit the entire Personal Raharja. Many ways in which to improve the quality of forcibly lectures in the learning process, techniques gamifikasi judged capable of being an effort to enhance the quality of the lectures in the learning. ZPreneur is able to realize the effort, because the ZPreneur apply the technique of gamifikasi with either Armo (AirzonE-Mall Money) are able to make student/i don't feel saturated and give change in the learning activities. The College currently Raharja already apply the learning to use the concept of Gamifikasithrough a website ZPreneur. Plus the design Viewboard Armo became complete as all user embodied in all viewboard armo and will motivate the user to always be no. 1 in viewboar armo.